Munda “Conversions” in Two Missionaries’ Narratives: A Moral and “Spiritual” Enlightenment and/or an Adaptive Answer to Colonial and Agrarian Change - Rousseleau, Raphaël (Social sciences and missions, 2024)
This article focuses on the conversion narratives of two fathers of the Belgian Jesuit mission in Bengal (India), Joseph Müllender and Johan-Baptist Hoffmann, among the Munda Adivasi minority. Their letters (1881–1927) offer contrasting accounts of conversion as motivated by preaching and the theological superiority of Christianity over so-called ‘spirit worship’ on the one hand, and by socio-political and agrarian issues as well as literacy on the other. Published material by Hoffmann (notably the Encyclopedia Mundarica, 1930–1937) completes our perspective on Munda cosmology and politics as on its Jesuit translation. Finally, an article from 1928 gives us the perspective of a young Jesuit-educated Adivasi on the same subject.